Associação de taninos condensados e fontes energéticas para novilhos de corte mantidos em pastagem hibernal em consórcio com leguminosas - Ortega Lopez, David Santiago (2022)
The objective of this work was to evaluate the effects of condensed tannins in two types of energy supplements (based on corn germ or soybean hulls) for beef steers kept on winter pasture intercropped with legumes. For all treatments, black oat (Avena strigosa), ryegrass (Lolium multiflorum Lam), and vesicular clover (Trifolium vesiculosum) pasture was used. The evaluated treatments were: Control (Black Oats + Ryegrass + Vesicular Clover); Cas + Tan (Pasture + energy supplementation based on soybean hulls with the addition of condensed tannin); Cas (Pasture + Soy-based energy supplementation); Ger + Tan (Pasture + energy supplementation based on corn germ with the addition of condensed tannin) and Tan (Pasture + energy supplementation based on corn germ). This work was carried out during 94 days (14 days of adaptation and 80 days of evaluations) using 36 Angus calves with an initial age of 6 ± 2 months and an average initial live weight of 178.06 ± 10.12 kg. The experimental area has 7.0 hectares, subdivided into 16 paddocks, of which 12 paddocks were approximately 0.35 hectares in size, and the other four were approximately 0.7 hectares in size. During the evaluation period, the animals were weighed at intervals of 21 days to adjust the supply of the supplement, and in the same interval the grazing simulation was performed. The experimental design used was randomized blocks in a 2 x 2 + 1 factorial scheme (two energy sources x with or without tannin + witness without supplementation), with three replications (paddocks). Energy supplementation (based on soybean germ or hulls) with condensed tannin did not increase the performance of the animals. However, energy supplementation made it possible to increase the productivity of the animals by 15%, corresponding to 0.166 kg per animal, the animal load by 60 kg of PV.ha-1, providing higher GPV.ha-1 (39 kg) and higher GPV.ha-1.day-1 (0.58 kg). The addition of condensed tannin in energy supplementation (based on corn germ and soybean hulls) does not increase animal performance when used at levels of 0.3% of live weight.